Enhanced performance of PV power control using model predictive control - Diaz Franco, Fernand; Vu, Tuyen V.; Gonsulin, David; Vahedi, Hesan; Edrington, Chris S. (Solar energy, 2017)
•A MPC approach to control the PV power is proposed.•PV power reference is calculated to achieve MPPT and reduce power mode.•The proposed method improves transient response. Fast MPPT. This paper focuses on the use of model predictive control (MPC) to control a DC/DC boost converter in order to regulate the PV power. When integrated with the grid, the PV system must deliver maximum power most of the time; however, if a voltage sag occurs, new grid codes demand that the control system should limit the PV power generated to avoid over current conditions and, consequently, a grid disconnection. Maximum and reduced power modes are implemented following the MPC strategy to achieve high–performance and stable operation in the system. First, the system is modeled in Matlab/Simulink and PLECS to understand its operation and to evaluate the effectiveness of the proposed algorithm. Secondly, experimental results are verified using the control hardware–in–the–loop (CHIL) approach on the Real Time Digital Simulator (RTDS).